Gender Dimorphism Does Not Affect Secondary Compound Composition in Juniperus communis After Shoot Cutting in Northern Boreal Forests - Stark, Sari; Martz, Françoise (Frontiers in Plant Science, 2018)
Due to a difference in plant resource allocation to reproduction, the males of dioecious plants may be more growth-orientated, whereas females may allocate more resources for synthesizing secondary compounds. This mechanism is considered to cause gender-specific differences in the plant responses to the loss of plant biomass. Here, we tested gender dimorphism in the responses of common juniper (Juniperus communis) to shoot cutting in four juniper populations located in northern boreal forests in Finland. We collected shoots from uncut junipers and from junipers subjected to shoot cutting in the previous year, and analyzed them for their shoot growth as well as phenolic and terpenoid concentrations. There were no differences in foliar phenolic or terpenoid concentrations between the males and the females. Shoot cutting increased phenolic but not terpenoid concentrations, similarly, in both males and females. Our study reveals that the nature of gender dimorphism may differ among species and locations, which should be considered in theories on plant gender dimorphism. Given the similar phenolic and terpene concentrations in both genders, the different sexes in the northern juniper populations might experience equal levels of herbivory. This lack of gender dimorphism in biotic interactions could result from the high need of plant secondary metabolites (PSM) against abiotic stresses, which is typical for juniper at high latitudes.